Expanding Horizons: Transitioning to Open Access - Radloff, Jeffrey (Innovations in Science Teacher Education, 2026)
We are pleased to announce that Innovations in Science Teacher Education (ISTE) is transitioning to the Public Knowledge Project’s Open Journal Systems open access platform. This transition is to increase access to ISTE internationally, broaden our diverse readership and contributions, and sustain our growth within the larger Asscoiation of Science Teacher Education (ASTE) organization. Together, we can adapt to the ever-changing educational landscape while widening our reach and impact. This editorial describes the changes and is a callout for new contributions.